Development of television rack from off-cut timber / Wan Jamalludin Wan Omar, Khairul Suhaimi Jusoh and Mohd Arshad Azmi - Wan Omar, Wan Jamalludin; Jusoh, Khairul Suhaimi; Azmi, Mohd Arshad (2011)
This project was conducted by [mal semester students of Diploma in Wood Industry. The objective of this study is to produce laminated off-cut timber using glue lamination technique. The total cost of raw material was RM25.67 while the total cost of part list included adhesive, finishing material and fastener was RM34.70. The percentage utilization of raw material, finishing's, fasteners and adhesive were 42%, 30%, 16% and 12% respectively. From the survey has been done, the most correspondence agreed that the price of TV rack made from laminated off-cut timber would be sale at price RM200-300. Therefore, this study has been developed TV rack which designed based on the customer's demand who want a simple product, light, modem and reasonable price. In addition the utilization of off-cut timber could value-added that material and reduced the wastage from sawmill.